Interrelation of galectin-3 and circulating proangiogenic endothelial cells in patients with ischemic chronic heart failure - A. A. Kremzer (Zaporozhye State Medical University, 2014)
Аim. Galectin-3 (Gal-3) is considered as a marker of nature progression of chronic heart failure (CHF) mediated cardiovascular remodelling. Progression of CHF associates with declining of circulating mononuclear progenitor cells (MPCs) in the peripheral circulation. The objective of this study was to evaluate the interrelationship between Gal-3 concentrations and proangiogenic MPCs in ischemic CHF patients. Design and Methods. The study population was structured retrospectively after determining the coronary artery disease (CAD) in 126 subjects (54 male), aged 48 to 62 years, with mild-to-severe ischemic CHF. The fl ow cytometric technique was used for predictably distinguishing cell subsets that depend on the expression of CD14, CD34, Tie-2, CD45, and CD309 (VEGFR2). Circulating Gal-3 level and NT-pro-BNP level was determined by ELISA method. Results. Elevated Gal-3 concentration more than 16.7 ng/ml associated with declined circulating MPCs. There was substantial negative effect of Gal-3 concentrations more than 16.7 ng/ml on circulating CD45+ CD34+ , CD45− CD34+ , CD14+ CD309+ , CD14+ CD309+ Tie2+, and NT-pro-BNP plasma level. Conclusion. Circulating level of MPCs progressively declines depending on the quartiles of Gal-3 concentration in CHF subjects.